FLORENTINO'S FAITHFULNESS AWAITING HIS FIRST LOVE IN MIKE NEWELL'S LOVE IN THE TIME OF CHOLERA MOVIE (2007): A PSYCHOANALYTIC APPROACH - KUSUMANINGTYAS, PRAVITA (2011)
The study is to reveal how the faithfulness waiting for the first love of the major character, Florentino Ariza, influences his personality. The objective of the study is to analyze the movie based on the structural analysis and the psychoanalityc analysis. This study is a qualitative study. The object of the study is Mike Newell's Love in the Time of Cholera. The data sources are divided into two, namely primary data source and secondary data source. In collecting the data, the researcher watches the movie and uses library research by collecting and selecting the appropriate data from many sources. The technique of the data analysis, is descriptive technique. After analyzing the movie of Mike Newell's Love in the Time of Cholera, the researcher concluded that there are several aspects of psychoanalytic approach of the major character. The aspects consist of id, ego and superego. The basic needs of Florentino Ariza consist of need of women touch, need of love and need of supporting friends. The expropriation of Florentino Ariza consist of job and women. The conflict of the three elements of Florentino Ariza personality occurs, influencing his mental condition and causing his faithfulness. Faithfulness occurs when the goal of the id is denied by the existence of some expropriations. It can be concluded that the cause of faithfulness is the goal of the id which is denied by some expropriation of his first love.